Time-frequency Domain Analysis of an Automobile Transmission - Ma Weijin; Wu Wenxuan; Wang Junyuan; Zhang Jipin (Jixie chuandong)
As a whole,the automobile transmission producing vibration and noise is an inevitable result under the action of exciting force,the bearing,shaft and box has influence on the vibration and noise of the gearbox. The time- frequency domain signal of a certain type of automobile transmission is collected and analyzed by means of simulation operation mode. Through the time- frequency domain analysis of vibration noise of automobile transmission,the vibration and noise characteristics can be controlled,a solid foundation for the follow- up of structural dynamics optimization design with the purpose of reducing vibration and noise is laid.